(untitled) (Innovaciones Educativas, 2021)
This study aims to develop, through a virtual environment, a space for the construction of meanings that are associated with the basic concepts of statistics, as part of the project Mathematical Learning Communities of the University of Costa Rica and the free courses it imparts. For this, from the socio-epistemological approach, the didactic engineering stages are developed to implement in a group of 30 students (between 14 and 15 years old) the statistical research cycle proposed by (Wild and Pfannkuch, 1999). The results show two organizational practices associated with the actions of the students when they understand behaviors of a stochastic nature. In addition, this research reports the role of change in the statistical sample, to ensure a representativeness of the population being studied. It concludes with some characteristics of inference practice and its relationship with a way of thinking about non-deterministic behaviors.